El oráculo del cemí: Ignacio de Loyola en la Columbeis de Giulio Cesare Stella - Díaz Gito, Manuel Antonio (Humanismo y pervivencia del mundo clásico. V: homenaje al profesor Juan Gil, 2015)
The Columbeis (London, 1585; Rome, 1589) by the Italian poet Giulio Cesare Stella (1564-1624) is the first fully epic Latin poem about Columbus’s heroic deeds. This article examines the poetic treatment of the ecclesiastical figure of Ignatius of Loyola in a passage of the poem as a way of emphasising the allegedly evangelical mission of Christopher Columbus.